Supported liquid membrane with strip dispersion for recovering indium from etching solution of LCD industry: influence of factors on performance - Ngan, Dang Thi Tuyet; Kien, Tran Trung; Wang, Da-Ming (Vietnam Journal of Science and Technology, 2021)
Supported liquid membrane with strip dispersion (SLMSD) is a promising process for metal recovery from e-waste or waste streams because of many advantages such as the ability to combine extraction and stripping into one single step and thus have non-equilibrium mass transfer characteristics and maximum driving force. This paper investigated the effect of important factors on SLMSD performance to recover indium from etching solution such as: pH of feed solution, extractant (Di-(2-ethylhexyl) phosphoric acid (D2EHPA)) concentration, oxalic acid concentration. It was found that 99.5 % In3+ was removed from feed solution in about 20 minutes with high concentration factor (4.5) under suitable conditions (pH 1; 0.6M Di-(2-ethylhexyl) phosphoric acid (D2EHPA), 2 wt% oxalic acid).